Exploring gait velocity as a predictor of cardiometabolic disease risk in young adults - Thorsen, Tanner; Oliveira, Nuno; Graybeal, Austin; Stavres, Jon (Frontiers in Sports and Active Living, 2024)
Background The association between poor gait and functional movement ability and metabolic syndrome (MetS) has been well established in older adults. A continuous cardiometabolic risk score, MetSindex, may more easily identify individuals at risk for cardiometabolic disease who do not yet meet the stringent criteria for a formal MetS diagnosis. Although the association between MetS and gait velocity is well established in older adults, no such relationship has been identified in younger adults; a group experiencing a rapid increase in the development of MetS. Methods MetSindex was determined for 21 young adults using standard procedures. Gait velocity was measured as participants completed a ten-meter walk test. Spatiotemporal parameters of gait were also derived using a motion capture system. Simple linear regression was used to determine the relationship between MetSindex and gait velocity, as well as MetSindex and spatiotemporal parameters of gait. Results There was a large inverse relationship between MetSindex and gait velocity. A large inverse relationship was also observed between MetSindex and cadence, and a large positive relationship was observed between stance time and double limb support time. Conclusions Gait velocity slows in young adults who do not necessarily meet the criterion for positive diagnosis of MetS—but demonstrate an increased risk for MetS and cardiovascular disease through higher MetSindex scores. The mechanism underlying reduced gait velocity may be fewer, but not shorter steps. Determining easy-to-use surrogates of MetS (e.g., gait velocity) may help combat the growing prevalence of MetS by increasing access to preventative approaches.